3 - L'hégémonie ethnique cyclique au nord Cameroun: 10.4314/ad.v24i1.22117 - Antoine Socpa, (Africa Development, 1999)
In North Cameroon, the oppositions between the main ethnic groups seem to follow different trajectories. For instance, the conflicts pitting the Arab Choa and Kotoko stem mainly from the 'autochtonous'/ 'allochtonous' divide, while those between Fulani and 'Kirdi' are based on a religious cleavage: Islam versus Paganism and Christianity. Beyond such primary semblances, the ethnic disparities in the access to or control over resources seem to be the common denominator to all conflict episodes, whether historic or recent, whether psychologically experienced or manifested in the form of violent confrontations. With data from the literature and from some rough observations of the political developments in North Cameroon, an attempt is made to analyse the economic, political and religious bases of ethnic conflicts in North Cameroon, as well as to show how, according to the different trajectories, the Arab Choa and Kotoko divide, the Fulani and Kirdi one, are constructed and used by socio-political and religious actors, resulting in a quasi-cyclical shift of power from one ethnic group to another.